2019
DOI: 10.24843/ejmunud.2019.v08.i06.p25
|View full text |Cite
|
Sign up to set email alerts
|

PERAN KEPUASAN PELANGGAN?MEMEDIASI?PENGARUH KUALITAS PELAYANAN?TERHADAP?LOYALITAS PELANGGAN PULL&BEAR KUTA – BALI

Abstract: This study aims to determine the effect of service quality on customer loyalty through customer satisfaction as a mediator. Respondents in this study were customers with a minimum level of education at least high school / equivalent who had conducted transactions at Pull & Bear Kuta - Bali more than once in the past year. The research sample was determined by 105 respondents using a sampling technique that is purposive sampling technique. The analysis technique used in this study is path analysis with clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…company profitability. This finding is in accordance with the research of Wiradarma and Suasana (2019) and Pahlawan et al, (2019) and the results of an analysis of service quality and customer loyalty through customer satisfaction empirically found that service quality has a positive effect on customer loyalty if mediated by customer satisfaction. Where the better the quality of service provided will be able to increase customer satisfaction and will increase customer loyalty.…”
Section: Customer Satisfactionsupporting
confidence: 92%
“…company profitability. This finding is in accordance with the research of Wiradarma and Suasana (2019) and Pahlawan et al, (2019) and the results of an analysis of service quality and customer loyalty through customer satisfaction empirically found that service quality has a positive effect on customer loyalty if mediated by customer satisfaction. Where the better the quality of service provided will be able to increase customer satisfaction and will increase customer loyalty.…”
Section: Customer Satisfactionsupporting
confidence: 92%
“…The results above indicate that customer satisfaction significantly mediates consumer loyalty which can be seen with a p-value of 0.000 (<0.05). This is in accordance with research by Wiradarma & Suasana (2019), which states that consumer satisfaction becomes a mediator and influences mediation on the quality of a service and consumer loyalty. El-Adly (2019) research states that customer satisfaction plays a fully or partially mediating role between the four dimensions of hotel perceived value and customer loyalty.…”
Section: Table 1 Average Variance Extracted (Ave) Valuesupporting
confidence: 91%
“…Penelitian ini bertujuan untuk menjelaskan: (1) pengaruh kualitas layanan terhadap kepuasan pelanggan, (2) pengaruh kualitas layanan terhadap word of mouth, (3) pengaruh kepuasan pelanggn terhadap word of mouth, (4) peran kepuasan pelanggan dalam memediasi pengaruh kualitas layanan terhadap kepuasan pelanggan, dan (5) menguji perbedaan tingkat kualitas layanan, kepuasan pelanggan, dan word of mouth antara klinik kecantikan Natasha Skin Care dan Erha Clinic. Studi empiris yang dilakukan oleh (Desiyanti et al, 2018;Anita & Rahanatha, 2019;Wiradarma & Suasana, 2019;Syahputra Pohan et al, 2020;Puspa, 2021;Sumargo, 2021;Mai & Cuong, 2021) menemukan bahwa kualitas layanan berpengaruh positif signifikan terhadap kepuasan pelanggan. Mengindikasikan bahwa perusahaan yang memiliki kualitas layanan lebih unggul dari pesaing maka akan memperoleh dan mempertahankan kepuasan pelanggan.…”
Section: Peran Kepuasan Pelanggan Memediasi Pengaruh Kualitas Layanan...unclassified